How Open Access Affects Competition in Scholarly Publishing Markets: A Tale of Good Intentions, Big Deals and Uncertain Outcomes - McCabe, Mark J. (Septentrio Conference Series, 2016)
Watch the VIDEO of the presentation. Since the 1990s a wave of innovation has transformed media markets, including those involving scientific communication. Expectations that the internet might improve access to the scientific literature while lowering costs to users have only been partially fulfilled. Using a modern economic framework I identify the historical, structural sources of market power in publishing markets and discuss the role that OA can play on a stage populated by publishers, authors, readers, and institutional actors of various types. For example, efforts to “flip” journals from a reader to author pay basis can follow a number of paths. At least one of these paths is efficient, lower cost, and plausible.